Reframing the photograph: confronting the Nazi past through artistic performance strategies since the 1960s - Allwork, Larissa (2015)
Working in a period when the western modernist focus on the originality of the artist, painterly form and composition had given way to more post Duchampian practices such as reappropriation, performance and the role of the spectator in creating artistic meaning, this paper will focus on works by Gerhard Richter, Anselm Kiefer and Gustav Metzger. This paper will evaluate how these artists perform the photograph in three divergent yet distinctly post-Duchampian ways in order to articulate challenging artistic languages which provoke confrontations with the Nazi past.